Development of liquid repellent coating on cotton fabric by simple binary silanization with excellent self-cleaning and oil-water separation properties. (1st February 2018) - Panda, Anita; Varshney, Priya; Mohapatra, Soumya S.; Kumar, Aditya
Highlights: Fabrication of superhydrophobic and superoleophobic coating on cotton fabric. Examine the chemical, thermal, mechanical, UV stability and stain resistance of the coating. Coated fabric exhibits excellent self-cleaning and oil-water separation properties. Abstract: This paper aims to develop a facile and single step method for the fabrication of superhydrophobic coating on cotton fabric. The coating has been prepared by using two silane trichloro(octadecyl)silane and (pentaflurophenyl)triethoxy silane by solution immersion technique. The wettability, surface topography and chemical compostion of the cotton fabric before and after treatment were charecterized by contact angle measurement, scanning electron microscope, and energy dispersive X-ray spectrum, respectively. Additionally, the functional group present in coating was analysed by FT-IR spectra. The coated fabric shows a contact angle of 172.9 ± 3°, 169 ± 3° and 167 ± 3° for water, ethylene glycol and glycerol, respectively. The chemical stability of the coated sample has been evaluated by immersion of the sample in different pH solutions and different solvents, showing the excellent chemical stability of coating. Ultrasonication with water, detergent and petroleum ether, and water jet impact test reveals the mechanical stability of coating. The thermal stability of the coated fabric has been examined by annealing the sample at different temperature. Additionally, it shows resistance to stain and UV irradiation. Furthermore, the coated cotton fabric exhibits excellent self-cleaning and oil-water separation properties, which makes it suitable for industrial applications.